2022
DOI: 10.3390/bs12030066
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Diet, Physical Activity, and Stress during the COVID-19 Pandemic: A Qualitative Analysis

Abstract: The COVID-19 pandemic has changed routines and habits, raising stress and anxiety levels of individuals worldwide. The goal of this qualitative study was to advance the understanding of how pandemic-related changes affected sleep, diet, physical activity (PA), and stress among adults. We conducted semi-structured, qualitative interviews with 185 participants and selected 33 interviews from a represented sample based on age, race, and gender for coding and analysis of themes. After coding for thematic analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In contrast, an American qualitative study (Orr et al, 2022) reported improvements in females’ diet during lockdown, despite decreased sleep quality and increased stress. Interestingly, participants reported stress and poor sleep quality as the key factors that led them to improve their diets; hence, the importance of managing stress as part of a holistic lifestyle intervention.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, an American qualitative study (Orr et al, 2022) reported improvements in females’ diet during lockdown, despite decreased sleep quality and increased stress. Interestingly, participants reported stress and poor sleep quality as the key factors that led them to improve their diets; hence, the importance of managing stress as part of a holistic lifestyle intervention.…”
Section: Discussionmentioning
confidence: 93%
“…Globalisation created a progressive cessation of the diet with a concurrent shift to the Western diet, which promotes weight gain, cancer and cardio-metabolic traits (Obeid et al, 2022). With more time at home during the COVID-19 lockdown periods, one would anticipate that individuals had more time to improve their health (Orr et al, 2022). However, impaired mental health and boredom may decrease the motivation for healthy lifestyle choices (Hossain et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 has not been associated with increase risk of narcolepsy (25), it has been suggested that infection with SARS-CoV2 may provide an opportunity to investigate mechanisms related to the development of narcolepsy (26). In a previous study examining the interaction between COVID-19 and multiple health behaviors (sleep, diet, and physical activity), the authors demonstrated increased vivid dreams and nightmares among 12% of participants and the majority were linked to increased stress and anxiety (75%) (27). These symptoms were predominantly reported by women.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, qualitative methods give a voice to participants, allowing researchers to take a closer look at people’s lived experiences and the factors surrounding them [ 27 ]. Qualitative methods have been used to understand the effect of the pandemic on sleep and uncovered insights that contextualized the findings of various epidemiological studies [ 28 ]. The pandemic engendered the opportunity to explore medical conditions against a unique backdrop.…”
Section: Introductionmentioning
confidence: 99%